2015
DOI: 10.1111/apt.13298
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term use of glucocorticoids and risk of peptic ulcer bleeding: a nationwide population‐based case‐crossover study

Abstract: SUMMARY BackgroundControversy exists regarding glucocorticoids therapy and the risk of peptic ulcer bleeding (PUB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A retrospective review of 92 haematology inpatients post chemotherapy found that 70% of patients with gut‐derived bacteraemia were on PPI therapy compared with 48% without bacteraemia, but confounding factors could not be excluded . A study in healthy volunteers which analysed gut flora pre‐ and post‐PPI therapy demonstrated changes in specific taxa, including Streprococcaceae and Enterococcaceae, which may lead to increased risk of Clostridium difficile infection …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review of 92 haematology inpatients post chemotherapy found that 70% of patients with gut‐derived bacteraemia were on PPI therapy compared with 48% without bacteraemia, but confounding factors could not be excluded . A study in healthy volunteers which analysed gut flora pre‐ and post‐PPI therapy demonstrated changes in specific taxa, including Streprococcaceae and Enterococcaceae, which may lead to increased risk of Clostridium difficile infection …”
Section: Literature Reviewmentioning
confidence: 99%
“…7 A study in healthy volunteers which analysed gut flora pre-and post-PPI therapy demonstrated changes in specific taxa, including Streprococcaceae and Enterococcaceae, which may lead to increased risk of Clostridium difficile infection. 40 Retrospective review of prescribing practices in clinical haematology at our institution Over the 14-months of our institutional retrospective review of PPI prescribing, 14 919 prescriptions were prescribed for PPI across all patients, 1123 of which were prescribed to haematology patients. Patients were grouped according to their disease state and the analyses of the appropriateness of PPI prescribing at the initiation and cessation of treatment showed that:…”
Section: Chemotherapy-related Mucositismentioning
confidence: 99%
“…No study investigated gastroprotective measures in glucocorticoid users specifically. The rationale for gastroprotective medication is given by the slightly increased risk for gastrointestinal adverse effects by treatment with glucocorticoids (relative risk: 1.1, CI: 0.5-2.1 [33] and odds ratio: 1.73, CI: 1.34-2.23 [34]) and the around threefold to fourfold increased risk when glucocorticoid treatment is combined with use of nonsteroidal anti- inflammatory drugs (NSAIDs) [33,34]. Several treatment regimens have been shown to be gastroprotective.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Several observational studies have described risk factors for NSAID‐induced upper GI complications expressed as odds ratios (OR) or relative risk (RR). Risk factors for NSAID‐induced upper GI complications include advanced age, history of peptic ulcer and concomitant therapy, including aspirin, other NSAIDs, anticoagulants or corticosteroids and SSRI . These risk factors are all well‐established, as are their relative risk measures.…”
Section: Introductionmentioning
confidence: 99%